ТРИСТУПЕНЕВА ЕЛЕКТРИЧНА МАШИНА З ВНУТРІШНІМ ТА ЗОВНІШНІМ РОТОРОМ: ПОРІВНЯЛЬНИЙ АНАЛІЗ ПОКАЗНИКІВ КЕРОВАНОСТІ - Пєтухов, І.С.; Кіреєв, В.Г.; Акінін, К.П.; Лавриненко, В.А. (Інститут електродинаміки НАН України, Київ, 2023)
Two structures of electric machines with three degrees of freedom of the rotational movement of the rotor are considered - with an external and an internal rotor held on an internal cardan suspension. A three-plane symmetric magnetic system was chosen for the comparative analysis and such a choice was justified. Limitations are formulated that allow considering the rotor as a conservative mechanical system, as well as considering the magnetic field in the electric machine as magnetostatic. Mathematical models of the rotational motion of a body with a fixed center of mass, as well as the force interaction of the magnetic field of a permanent magnet located on the rotor and the control winding located on the stator, are given. The peculiarities of the distribution of electromagnetic forces in both structures are analyzed and the greater efficiency of the formation of these forces in the structure with an internal rotor is shown. Expressions for the components of the electromagnetic moment for use in the "COMSOL Multiphysics" interface are obtained. Forced precession movement for both structures was analyzed in the case of equal radii of the control windings and in the case of the same dimensions of the magnetic systems. It was determined that the structure with an external magnetic circuit is able to provide an order of magnitude smaller angular velocity of precessional movement and, at the same time, an equally smaller range of nutation. References 14, figures 10.